Principles of fraud examination - Wells, Joseph T. (Hoboken, N.J. : Wiley, 2010)
'Accountants need to have a strong understanding of fraud - what it is and how it is committed, prevented, and resolved. The third edition provides them with that knowledge. It documents the schemes used by executives, managers, and employees to commit fraud against their organisations. Case studies, complete with statistics and flowcharts, are provided for each chapter. A new chapter is included on fraud risk assessment. Updated statistics are presented on recent ACFE findings. In addition, minor revisions throughout focus on the increasing use of electronic payments and other technology in fraud schemes. This helps accountants detect and prevent fraud'--
Machine generated contents note: CHAPTER 1 Introduction. -- CHAPTER 2 Skimming. -- CHAPTER 3 Cash Larceny. -- CHAPTER 4 Billing Schemes. -- CHAPTER 5 Check Tampering. -- CHAPTER 6 Payroll Schemes. -- CHAPTER 7 Expense Reimbursement Schemes. -- CHAPTER 8 Register Disbursement Schemes. -- CHAPTER 9 Noncash Assets. -- CHAPTER 10 Corruption. -- CHAPTER 11 Accounting Principles and Fraud. -- CHAPTER 12 Fraudulent Financial Statement Schemes. -- CHAPTER 13 Fraud Risk Assessment. -- CHAPTER 14 Conducting Investigations and Writing Reports. -- CHAPTER 15 Interviewing Witnesses. -- CHAPTER 16 Occupational Fraud and Abuse: The Big Picture. -- APPENDIX A Commercial Online Services. -- APPENDIX B Sample Code of Business Ethics and Conduct. -- APPENDIX C Fraud Risk Assessment Tool. -- BIBLIOGRAPHY. -- INDEX.
Includes bibliographical references and index.
Keywords: Fraud; Fraud investigation; Fraud -- Prevention; Auditing, Internal; BUSINESS & ECONOMICS / Auditing